Wealth, Violance and Status: Lay and Ecclesiastical Élites in the Middle Loire Valley, c. 850- c. 1150 - Ó SÚILLEABHÁIN, NIALL (Trinity College Dublin. School of Histories & Humanities. Discipline of History, 2020)
Interpretations of the period following the disintegration of the Carolingian empire in Western Europe at the end of the ninth century have long divided historians, between those who believe a violent rupture in political and social structures took place around the year 1000 and those who argue for an essential continuity. This thesis aims to transcend these debates, by approaching medieval society through a case-study in the Loire valley region relying on two fresh methodological insights. Firstly, it will investigate changes in the economic structures which provided society's material base; secondly, it will analyse how those élites claimed, performed and maintained their status. Based on these two approaches, the thesis explores changing patterns of élite behaviour in order to better understand the social and economic changes which took place from the late ninth century onwards. The thesis examines the effects of shifting landholding patterns, the emergence of seigneurial customs, changing attitudes to church patronage and lay violence, and the methods by which élites were identified in documents, to establish their implications for the ways by which élites could claim and maintain their status. It concludes that there was a significant and fundamental transformation of social and economic structures, beginning in the middle of the tenth century, in the middle Loire valley, although the pace of change is slower than would be appropriate for a 'Feudal Revolution'. Nevertheless, the breakdown of the Carolingian political order unleashed a wave of competition amongst local and regional élites, which saw them innovate and adapt the heritage of Carolingian culture to create a new, 'feudal' social order. This was fuelled by the changes in economic structures which provided élites with more wealth to promote their own status; the competition for status in turn fuelled élites' need for more wealth and their incentive for economic expansion.
APPROVED
Keywords: Medieval France; French History; Social History; Economic History; Medieval Church; Aristocracy; Feudal; Medieval History